2018
DOI: 10.1111/psyp.13083
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cognitive training on spontaneous gamma oscillations in schizophrenia

Abstract: Schizophrenia patients exhibit less gamma-frequency EEG/MEG activity (>30 Hz), a finding interpreted as evidence of poor temporal neural organization and functional network communication. Research has shown that neuroplasticity-oriented training can improve task-related oscillatory dynamics, indicating some reorganization capacity in schizophrenia. Demonstrating a generalization of such task training effects to spontaneous oscillations at rest would not only enrich understanding of this neuroplastic potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Baseline gamma-evoked power may be an index of the brain's overall "adaptive integrity" in these lower-level perceptual networks as the patients with the largest ASSR responses had more robust cognitive gains in response to TCT 39,44,61 . Previous studies support the notion that auditory-based TCT mediates its therapeutic effects on neurocognition by inducing neuroplastic changes in distributed frontal-temporal and thalamocortical circuits 25,[62][63][64][65] . Indeed, training-induced changes in oscillatory activity and event-related potentials have been shown to correlate with TCT-induced cognitive enhancements 62,65 .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Baseline gamma-evoked power may be an index of the brain's overall "adaptive integrity" in these lower-level perceptual networks as the patients with the largest ASSR responses had more robust cognitive gains in response to TCT 39,44,61 . Previous studies support the notion that auditory-based TCT mediates its therapeutic effects on neurocognition by inducing neuroplastic changes in distributed frontal-temporal and thalamocortical circuits 25,[62][63][64][65] . Indeed, training-induced changes in oscillatory activity and event-related potentials have been shown to correlate with TCT-induced cognitive enhancements 62,65 .…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies support the notion that auditory-based TCT mediates its therapeutic effects on neurocognition by inducing neuroplastic changes in distributed frontal-temporal and thalamocortical circuits 25,[62][63][64][65] . Indeed, training-induced changes in oscillatory activity and event-related potentials have been shown to correlate with TCT-induced cognitive enhancements 62,65 . These training-related effects on gamma activity (i.e., the pre-post difference scores after 30-50 hours of TCT) have been shown to correlate with improvements in executive function and other cognitive domains 62,65 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Studies investigating pre-stimulus or pre-trial spontaneous neural activity in reference to subsequent activity demonstrate both complex correlates of subsequent stimulus-evoked neural activity 1 and cognitive behavioral output such as biasing subsequent perceptual inference 6 . In parallel, other studies have shown differences in long time scale spontaneous resting activity between neurotypical and cognitively disabled individuals, such as a decrease in gamma power in individuals with schizophrenia with poor cognitive performance 7 , and alterations in resting state regional activity patterns among Down syndrome patients with cognitive impairment 8 . Further insights into how the brain may be functionally organized to drive subsequent behavior can be gleaned from proactive cognitive control, a major subdivision of cognitive control 9 , whereby neural mechanisms actively maintain relevant information in working memory, trigger goal representations, and coordinate the attention, perception, and action systems in anticipation of subsequent goal-directed activity 10,118 .…”
Section: Introductionmentioning
confidence: 82%
“…Over the last 10 years there has been increased interest in clinical trials seeking to use neural measures to demonstrate biological effects of psychological and biological treatments. As an example, there is considerable research examining gamma‐band activity (30 to 50 Hz) in SCZ, with the hypothesis that gamma abnormalities are due, in part, to inhibitory interneuron dysfunction, and with clinical trials examining the effectiveness of cognitive therapy, physical exercise, or pharmacology for normalizing gamma activity …”
Section: Auditory Encoding Measures In Sczmentioning
confidence: 99%